Determinants of Islamicity Performance Index (IPI) Factors on Islamic Banking Growth with Audit Quality as a Moderation Variable - Safitri, Vita Intan; Mappanyukki, Ratna (Journal Research of Social Science, Economics, and Management, 2025)
Islamic banking in Indonesia is expected to make a significant contribution to the national economy. With the majority Muslim population and a proven ability to remain resilient during economic crises, the market share of Islamic banks should ideally grow more rapidly compared to conventional banks. However, as of 2022, the market share of Islamic banking in Indonesia had only reached around 7.09%, far behind Malaysia, which achieved 36.3%. This indicates the presence of structural challenges and persistent public perceptions that hinder growth, making it crucial to analyze the factors influencing the development of Islamic banking, as proxied by market share. This study aims to examine the influence of the Islamicity Performance Index (IPI)—consisting of Profit Sharing Ratio (PSR), Zakat Performance Ratio (ZPR), Equitable Distribution Ratio (EDR), and Islamic Income vs Non-Islamic Income (II vs NII), on the growth of Islamic banking in Indonesia. In addition, this research investigates the moderating role of audit quality. The data used are secondary data from the annual reports of Islamic Commercial Banks (BUS) registered with the Financial Services Authority (OJK) during the 2018–2022 period, selected through purposive sampling. The analysis was conducted using Moderated Regression Analysis (MRA) with the assistance of EViews software. The findings reveal that most variables of the Islamicity Performance Index (PSR, ZPR, EDR, INII) do not significantly affect the growth of Islamic banking, either directly or through the moderation of audit quality.